Pengaruh Pengelolaan Keuangan dan Sistem Akuntansi Keuangan Terhadap Kualitas Laporan Keuangan - Dora Devita; Dewi Zulvia (International Forum of Researchers and Lecturers, 2023)
ThisThis study aims to examine financial management and financial accounting systems on the quality of financial reports. Collecting research data using a questionnaire. Questionnaires were delivered to 35 employees of the Office of Manpower and Transmigration of West Sumatra Province. This research is included in quantitative research. The sample was determined using total sampling technique. Data analysis used multiple regression using SPSS 22 software. The results of this study indicate that financial management has a positive effect on the quality of financial reports and the financial accounting system cannot influence the quality of financial reports.